(untitled) (Malay Literature, 2017)
This article discusses the manuscript of Hikayat Kelana Sita Kembara, a Malay panji tale held in the collection of the Pusat Dokumentasi Melayu in Dewan Bahasa dan Pustaka, Kuala Lumpur, under the call number MS 46. To date, no studies or critiques have been published about this manuscript. Through transliteration of the text and analysis of its content, any features of Malay panji tales it contains can be assessed by considering three basic differences between Javanese and Malay panji tales, that is, by referring to existing classifications, language use and local elements. Based on the abovementioned method of research, the researcher also aims to scrutinize, identify and discuss the features of Malay panji tales that are found in Hikayat Kelana Sita Kembara and other Malay panji tales, namely Hikayat Misa Taman Jayeng Kesuma and Hikayat Chakel Waneng Pati. This is to invite further discussion of Hikayat Kelana Sita Kembara in the study of Malay literature. Keywords: Panji tales, Malay panji tales, Hikayat Kelana Sita Kembara, features of Malay panji tales, language use, local elements